DYNAMICS OF PADDY CULTIVATION IN KERALA - Mukesh K (EPRA: International Journal of Economic and Business Review, 2015)
In recent years Kerala agricultural production is low level but it may be given a threat to Kerala food security. Kerala Economy is depending on central government share and other neighboring states like Tamilnadu Karnataka and Andhra Pradesh for the sustainable food balance. It gives us Kerala economy is deficit economy in every year. In India have passed the food security bill Loksabha in 2014 may reduce the state share, because the standard of living of people in Kerala is high comparatively other states in India. A lot of agricultural fields are filled for the developmental activities like metro rail, airport, and industries; housing plots, etc...The main agricultural production district in Kerala is Palakkad and Alappuzha. Large number of cancer patients is in Kerala due to the cause of poisoned foods in other states. Rice production in Kerala has given declining tendency to the recent year 2012-13 is 6%. Main important causes for the declining tendency of rice production in Kerala were low price in output has given to the farmers and there was not profitable because Kerala climate has no similarity in each and every year. Government has not given a serious intervention to rice production.